Disaster Mitigation Education: Challenges and Opportunities in Six Areas of PAUD Development - Zuama, Shofiyanti Nur (International Journal on Advanced Science, Education, and Religion, 2024)
This article discusses disaster mitigation education, looking at the challenges and opportunities in six areas of PAUD development. The method used is qualitative research in the nature of library research, using books and other literature as the main object. Research data is in the form of library data that has been selected, searched, presented and analyzed. The definition of disaster mitigation education is an individual's efforts to prepare themselves and their potential, process and mature their feelings, thoughts, will, as well as increasing skills or abilities in facing or minimizing the risk of disasters that will occur. An overview of disaster mitigation education, viewed from six areas of PAUD development, namely religious and moral values, physical motor, cognitive, language, social emotional, and arts. The challenges and opportunities that children learn, to stimulate and train appropriate and appropriate behavior, so that good habits are formed in children so that when a disaster occurs, children become individuals who can more easily work together in reducing the risk of disasters or minimizing damage or injury that could occur. happen. Children who are equipped with attitudes and actions that are trained consistently in six areas of development will become children who provide strength and entertainment for their parents during difficult and sad conditions, children will also be able to express their feelings and thoughts appropriately, be responsive, and be more responsive to disasters. , instead of the child crying hysterically or becoming a burden on the parents when the child is difficult to control or becomes more panicked, it actually approaches danger.